Zaupanje otroka drugi osebi - aktualni problemi - Končina Peternel, Mateja (Pravni letopis, 2009)
According to the decisions of the Constitutional Court of the RS in cases No. U-I-273/98 in U-I-312/00 the legislator has only partial amended the Marriage and Family Relations Act. That is a reason why regulation is not harmonized and does not give basis for the effective protection of the child in need. In new Family Code the jurisdiction for the application of all measures for the protection of child should be transferred to the court (except emergency measures). The jurisdiction for making decisions about the type of substitute care (fostering, guardianship, registered children's homes) should be regulated consistently. It is necessary to link all the measures for the protection of children according to the Violence Protection Act, Family Code and Police Act into a harmonized system. The procedure in family matters is now regulated partially in the Marriage and Family Relations Act, partially in the Civil Procedural Act. It should be amended and regulated only in Procedural Acts or in a special chapter of Family Code.
Keywords: child; človekove pravice; družinsko pravo; human rights; otroci; posvojitev; rejništvo; starševstvo; starši